FINANCIAL LITERARY AMONG COLLEGE STUDENTS - Jacob, Meenu Susan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Financial literacy stands as a fundamental ability that affects how college students behave with their money and make choices about decisions as well as future financial security. The study reveals that financial literacy reaches a moderate level in 56% of students yet Business & Economics students maintain 72% while STEM students have 58% and Humanities students demonstrate 48%. The study shows that budgeting occurs among 42% of students and regular saving takes place among 38% of students yet impulse spending affects 55% of students. The insufficient financial education of students remains a critical issue because students who receive formal financial training achieve better scores in financial literacy tests but represent only 29% of the student population. The study relies on quantitative methods with 400 college participants representing various fields through structured questionnaire data analyzed for financial literacy and behavior evaluation. Statistical analysis shows that responsible financial behavior possesses a significant connection (r = 0.67, p < 0.01) to the financial literacy levels of participants. The author suggests implementing financial literacy programs throughout different academic subjects while using fintech tools for education and treating financial anxiety which affects 45% of students and promoting family discussions about money management. Structured educational programs along with digital financial tools can produce students who acquire essential financial abilities and achieve stress reduction for better long-term financial wellness which creates a society built on responsibility and economic resilience.